Role of β3-Adrenergic Receptor in Bone Marrow Transplant as Therapeutical Support in Cancer - Nastasi, Nicoletta; Bruno, Gennaro; Favre, Claudio; Calvani, Maura (Frontiers in Oncology, 2022)
β3-adrenergic receptor (β3-AR) is the last β-adrenoceptor subtype identified. β3-AR is widely expressed and regulates numerous physiological processes, and it is also a potential target for the treatment of many diseases, including cancers. For some types of cancers, bone marrow transplant (BMT) represents a valid therapeutic support, especially in the case of the necessity of high-dose chemotherapy and radiotherapy. For a successful BMT, it is necessary that a donor’s hematopoietic stem cells (HSCs) correctly reach the staminal niche in the recipient’s bone marrow (BM) and contribute to restore normal hematopoiesis in order to rapidly repopulate BM and provide all the healthy blood cells of which the patient needs. Generally, it takes a long time. Control and accelerate homing and engraftment of HSCs could represent a helpful approach to avoid the complications and undesirable effects of BMT. The evidence that the β-adrenergic system has a role in the BM can be found in different studies, and this leads us to hypothesize that studying this field could be interesting to meliorate the most critical aspects of a BMT. Here, we collected the data present in literature about the role of β3-AR in the BM with the purpose of discovering a possible utility of β3-AR modulation in regulating HSC trafficking and hematopoiesis.